Antimicrobial Potential of Bempedoic Acid as a Gastroprotective Agent - Sharma, Ketan; Sharma, Anuj Kumar; Murti, Yogesh; Yadav, Sachdev; Ved, Akash; Kulshreshtha, Mayank (Anti-Infective Agents, 2026)
IntroductionBempedoic acid (BA) is a well-known lipid-lowering agent which inhibits the HMG-CoA reductase enzyme. It contains various chemical groups in its structure, which are responsible for antimicrobial potential. The study investigates the antimicrobial activity of BA against pathogenic bacteria, including Bacillus subtilis, Enterococcus faecalis, Salmonella typhi, and Staphylococcus aureus.MethodsThe disc diffusion method was employed for this study. Initially, Mueller Hinton Agar (MHA) was prepared according to the standard formulation provided by Himedia. Specifically, 38 grams of MHA powder was dissolved in 1 liter of distilled water. The medium was then sterilized by autoclaving at 121°C and 15 psi for 15 minutes using an autoclave (Gentek India Pvt. Ltd.). After sterilization, the medium was poured into sterile glass Petri dishes inside a laminar airflow cabinet (Toshiba, India) under aseptic conditions, with each plate receiving 30 ml of the medium. The plates were left to solidify in the laminar flow. Once solidified, the bacterial inoculum was evenly spread across the surface of the agar using a sterile cotton swab. Ten minutes after inoculation, discs were placed onto the agar using sterile forceps. Each disc was loaded with 25 μl of sample at three different concentrations: 100 mg/ml, 50 mg/ml, and 25 mg/ml. The samples were allowed to diffuse into the agar, after which the plates were sealed with parafilm and incubated at 37°C for 24 hours.ResultsBA lacked significant activity against Bacillus subtilis but exhibited notable inhibition against Enterococcus faecalis (zone of inhibition: 11 ± 0.00 mm at 50 mg/kg), Salmonella Typhi (10 ± 0.00 mm at 50 mg/kg and 100 mg/kg), and Staphylococcus aureus (significant activity at 100 mg/kg).DiscussionComparative analysis revealed BA exhibited efficacy comparable to that of ciprofloxacin in certain cases. Molecular studies highlighted BA's ability to mitigate bacterial virulence by disrupting mechanisms, such as pro-inflammatory protein synthesis and mitochondrial genomic integrity, especially in Enterococcus faecalis. These findings underscore BA’s selective antimicrobial properties, suggesting its potential for therapeutic application in managing polymicrobial infections, gastrointestinal pathologies, and systemic diseases.ConclusionThe pharmacodynamic profile suggests BA exerts its antimicrobial effects by targeting bacterial virulence mechanisms, including the suppression of pro-inflammatory responses and the disruption of mitochondrial genomic stability. These attributes position BA as a promising candidate for further pharmacological development, especially as a potential adjunct to conventional antibiotics for managing drug-resistant and opportunistic infections. Further in vivo validation and clinical studies are warranted to establish its therapeutic potential and safety profile.
Keywords: Salmonella Typhi